Reflexões sobre a educação ambiental no ensino superior do estado do Paraná - Oliveira, Cinthia Raquel Pergentino de (2010)
Capra (2006) has suggested that the more we study the mayor problems of our time, the more we come to realize that they cannot be understood in isolation. They are systemic problems, which mean that they are interconnected and interdependent. These problems must be seen as just different facets of one single crisis, which is largely a crisis of perception. The solutions of these problems require a radical shift in our perceptions, our thinking, and our values in our Ecological Thinking. The discussion of this work is based on the Ecological Thinking and its actions, by the ideology (Ecologism) and the ecological movements that are showing its insertion in Geography teaching by the Environmental Education, especially in the universities. In this context, the present work has the main objective to research how the Environmental Education is being worked on and to understand the reasons of your insertion in the academic Geography. The universities chosen were: UFPR (Universidade Federal do Paraná), UEM (Universidade Estadual de Maringá) and UEL (Universidade Estadual de Londrina). The choice of these universities is based upon the oldest academic Geography graduations in the Paraná State. The results show that, with all observations and questions, the Ecological Thinking are made part of the respondents answers and their teaching activities, but it is not, as with the same intensity in their daily practices.